Strategi Normativitas Pembatasan Terpidana dalam Proses Pemilihan Umum di Indonesia - Karnoto Karnoto (JIL : Journal of Indonesian Law, 2020)
The polemic of ex-convict candidates for legislative members has given special attention to academics and the general public. In this case, the polemic lies in the overlap between regulations number 7 of 2017 about General Elections and Regulation of Election Commission number 20 of 2018 about the nominations of DPR, provincial DPRD and Regency / city DPRD members. The core problem in the regulation is the limitation of political rights for ex-convicts (Croupier of Drugs, Sexual Crimes against Children and Corruption). Whereas the higher level regulation does not limit this. This research is a library research. Namely research that uses all sources of research from books, journals, articles, research, laws, and from the internet. After the sources are obtained and then analyzed using related theories. This research focuses on the normativity strategy that should have been carried out and applied by the general election commission in limiting former convicts in the 2019 general election. The normativity strategy that should be carried out by the general election commission on the limitation of convicted persons in general elections in Indonesia is the making of regulations relating to the submission of honesty to the public that those who nominate themselves as prospective legislative candidates are ex-convicts. One of the strategies that must be regulated in the regulation is, Submission to the public through social media, in this case the delivery must be regulated more stringently and in more detailed procedures, because it is feared that political actors whose status as ex-convicts only pay to one television station and get a certificate or proof. However, the provision of information is not broadcast on the television station, and so forth.